LB-17. Efficacy of Hydroxychloroquine (HCQ) for Post-exposure Prophylaxis to Prevent Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection: A Blinded, Randomized, Controlled Trial. (31st December 2020) - Brown, Elizabeth R; Bershteyn, Anna; Karita, Helen C Stankiewicz; Johnston, Christine; Thorpe, Lorna; Kottkamp, Angelica; Neuzil, Kathleen; Laufer, Miriam K; Deming, Meagan; Paasche-Orlow, Michael K; Kissinger, Patricia J; Luk, Alfred; et al.
Abstract: Background: Prevention interventions for coronavirus disease (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), are currently limited to non-pharmaceutical strategies. Observational and laboratory data suggested that hydroxychloroquine (HCQ) had biologic activity against SARS-CoV-2. A blinded trial of HCQ in persons with confirmed exposure and virologic and clinical endpoints is needed. Methods: We conducted a national, householdrandomized, double-blind, controlled trial of HCQ post-exposure prophylaxis, with entirely remote study procedures. We enrolled close contacts exposed to persons with SARS-CoV-2 infection in the past 96 hours. Participants were randomized to either HCQ (400 mg daily for three days followed by 200 mg daily for eleven days) or ascorbic acid (500 mg followed by 250 mg daily), as a placebo-equivalent control. Participants self-collected mid-turbinate swabs daily (days 1–14) for SARS-CoV-2 PCR testing. The primary outcome was PCR-confirmed, incident SARS-CoV-2 infection among persons SARS-CoV-2 negative at enrollment. Symptoms were assessed using criteria from the US CDC. Results: From March-August 2020, 623 households were randomized; 311 households (381 participants) to the HCQ group and 312 households (400 participants) to the control group. Ninety- one percent of participants were retained up to day 14 and 9, 595 of 10, 588 (91%) of swabs were tested. Among participants who were SARS-CoV-2 negative at baseline (n=626/781, 80%), the cumulative incidence of SARS-CoV-2 was 14.5% (95% CI: 11.6–17.4) and the cumulative incidence of COVID-19 symptoms was 11.6% (95% CI: 8.9–14.2) at day 14. By day 14, there was no difference between the HCQ group and control group in SARS-CoV-2 acquisition (46 vs. 43 events, aHR= 0.99, 95% CI 0.64–1.52, p=0.95) or symptomatic disease (40 vs. 32 events, aHR= 1.23, 95% CI: 0.76–1.99, p=0.40). The adverse event frequency was similar between groups (59 [15.5%] participants in the HCQ and 45 [11.3%] in the control group, p=0.092). Cumulative incidence of RT-PCR-confirmed SARS-CoV-2 infection among close contacts of diagnosed cases, by study group Conclusion: This randomized, double-blind, controlled trial among persons with recent exposure and high incidence of SAR-CoV2 provides strong evidence that HCQ post-exposure prophylaxis did not prevent SARS-CoV-2 infection or modify clinical disease. Disclosures: Anna Bershteyn, PhD, Bill and Melinda Gates Foundation (Grant/Research Support)Gates Ventures (Consultant)National Institutes of Health (Grant/Research Support) Kristopher M. Paolino, MD, MTM&H, Nothing to disclose Raphael J. Landovitz, MD, MSc, Gilead (Advisor or Review Panel member)Merck (Advisor or Review Panel member)Roche (Other Financial or Material Support, Speaker Honoraria) Anna Wald, MD, MPH, Aicuris (Individual(s) Involved: Self): Consultant; Gilead (Individual(s) Involved: Self): Consultant; GlaxoSmithKline (Individual(s) Involved: Self): Scientific Research Study Investigator; Merck (Individual(s) Involved: Self): DSMB participation; provision of vaccine for a study, Other Financial or Material Support; Sanofi (Individual(s) Involved: Self): Scientific Research Study Investigator; X-Vax (Individual(s) Involved: Self): Consultant Helen Y. Chu, MD MPH, Cepheid (Grant/Research Support)Ellume (Grant/Research Support)Glaxo Smith Kline (Consultant)Merck (Consultant)Sanofi-Pasteur (Grant/Research Support)